Regional variation in cardiac implantable electronic device implants trends in New Zealand over the past decade (ANZACS‐QI 54). Issue 6 (31st May 2022) - Foo, Fang Shawn; Poppe, Katrina K.; Lee, Mildred; Clare, Geoffrey C.; Stiles, Martin K.; Looi, Khang‐Li; Webber, Matthew; Boddington, Dean; Jackson, Rod; Kerr, Andrew J.
Abstract: Background: Permanent pacemaker (PPM) and implantable cardioverter defibrillator (ICD) implant rates have increased in New Zealand over the past decade. Aims: To provide a contemporary analysis of regional variation in implant rates. Methods: New PPM and ICD implants in patients aged ≥15 years were identified for 10 years (2009–2018) using procedure coding in the National Minimum Datasets, which collects all New Zealand public hospital admissions. Age‐standardised new implant rates per million adult population were calculated for each of the four regions (Northern, Midland, Central and Southern) and the 20 district health boards (DHB) across those regions. Trend analysis was performed using joinpoint regression. Results: New PPM implant rates increased nationally by 3.4%/year ( P < 0.001). The Northern region had the highest new PPM implant rate, increasing by 4.5%/year ( P < 0.001). Excluding DHB with <50 000 people, the new PPM implant rate for 2017/2018 was highest in Counties Manukau DHB (854.3/million; 95% confidence interval (CI): 774.9–933.6/million) and lowest in Canterbury DHB (488.6/million; 95% CI: 438.1–539.0/million). New ICD implant rates increased nationally by 3.0%/year ( P = 0.002). The Midland region had the highest new ICD implant rate, increasing by 3.8%/year ( P = 0.013). Excluding DHB with <50 000 people, the new ICD implant rate for 2017−2018 was highest in the Bay of Plenty DHB (228.5/million; 95% CI: 180.4–276.6/million) and lowest in Canterbury DHB (90.2/million; 95% CI: 69.9–110.4/million). Conclusion: There was significant variation in PPM and ICD implant rates across regions and DHB, suggesting potential inequity in patient access across New Zealand.